Evaluation of the ICT Malaria P.f/P.v and the OptiMal Rapid Diagnostic Tests for Malaria in Febrile Returned Travellers - Playford, E. Geoffrey (American Society for Microbiology, 2002)
Rapid diagnostic tests (RDTs) are less reliant on expert microscopy and have the potential to reduce errors in malaria diagnosis but have not been extensively evaluated in nonimmune persons or in countries where infection is not endemic. We evaluated the ICT P.f/P.v (ICT-Amrad, Sydney, Australia) and OptiMal (Flow Inc., Portland, Oreg.) assays prospectively for the diagnosis of malaria in 158 specimens from 144 febrile returned travellers in Australia by using expert microscopy and PCR as reference standards. Malaria was diagnosed in 93 specimens from 87 patients by expert microscopy, with 3 additional specimens from recently treated patients testing positive for Plasmodium falciparum by PCR. For the diagnosis of asexual-stage P. falciparum malaria, the sensitivity and specificity of the ICT P.f/P.v assay were 97 and 90%, respectively, and those of the OptiMal assay were 85 and 96%, respectively. The ICT P.f/P.v assay missed one infection with a density of 45 parasites/μl, whereas the OptiMal assay missed infections up to 2,500/μl; below 1,000/μl, its sensitivity was only 43%. For the diagnosis of P. vivax malaria, the sensitivity and specificity of the ICT P.f/P.v assay were 44 and 100%, respectively, and those of the OptiMal assay were 80 and 97%, respectively. Both assays missed infections with parasite densities over 5,000/μl: up to 10,000/μl with the former and 5,300/μl with the latter. Despite the high sensitivity of the ICT P.f/P.v assay for P. falciparum malaria, caution is warranted before RDTs are widely adopted for the diagnosis of malaria in nonimmune patients or in countries where malaria is not endemic.